3D-printed TiO2-Ti3C2Tx heterojunction/rGO/PDMS composites with gradient pore size for electromagnetic interference shielding and thermal management. (September 2022) - Liu, Guangde; Yu, Rongrong; Liu, Dong; Xia, Yuanhua; Pei, Xiaoyuan; Wang, Wei; Min, Chunying; Liu, Shengkai; Shao, Ruiqi; Xu, Zhiwei
Highlights: 3D gradient pore size structure effectively optimizes impedance matching. The internal mesoporous structure enhances the multiple reflection loss. TiO2 -Ti3 C2 Tx realized the synergistic effect of dielectric loss and dipole loss. TiO2 -Ti3 C2 Tx /rGO/PDMS composites has ultra-high EMI SE and electric/photo-thermal conversion effect. Abstract: In this paper, the Ti3 C2 Tx /GO frame with vertical pore gradient is constructed by using 3D printing technology. The TiO2 -Ti3 C2 Tx heterojunctions is generated in situ by thermal annealing to control the oxidation of 3D frames. TiO2 -Ti3 C2 Tx /rGO/PDMS composites with high EMI SE and excellent thermal management performance are assembled by curing the annealed 3D frame with polydimethylsiloxane (PDMS). Notably, the composites have a unique multilayer-scale structure that rod-shaped TiO2 particles are decorated on Ti3 C2 Tx substrate and TiO2 -Ti3 C2 Tx /rGO stack to form an amorphous porous gradient pore size structure. The effect of gradient pore size on EMI SE of composites is studied by simulation. Under the synergistic effect of multiple loss mechanism, the designed composites show conductivity of up to 173.1 S/m, the thickness of the composite is 2 mm and the density is 67 mg/cm 3, which shows excellent EMI SE of 58 dB. The composites also have excellent thermal management performance.